[Students in costume for 'Dutch Dance' performed at annual Athletic Carnival.] - Frank Aston::::::photographer::: (1914)
Mar. 6, 1914. Students in costume for 'Dutch Dance' performed at annual Athletic Carnival. ('No. 1' -- Students lined up in one row; each with hands on shoulders of the girl ahead) Published in Polytechnic J. 1914. Photo was taken outdoors but actual performance was given in the dining hall.